From Samarqand to Toledo
1 online resource
Keywords: Documents open up another an approach complementary to the overwhelming richness of literary tradition as preserved in manuscripts. This volume combines studies on Greek, Sogdian and Arabic documents (letters, legal agreements, and amulets) with studies on Arabic and Judeo-Arabic manuscripts (poetry, science and divination).